Tetraarylpyrrolo[3,2-b]pyrrole-BODIPY dyad: a molecular rotor for FRET-based viscosity sensing - Agrawal, Richa; Gorai, Sudip; Yadav, Sunil Suresh; Wadawale, Amey P.; Mula, Soumyaditya (Frontiers in Chemistry, 2024)
With the aim to develop a FRET-based viscosity sensor, two dyad molecules, 4 and 5, comprising tetraarylpyrrolo[3,2-b]pyrrole (TAPP) (donor) and naked boron-dipyrromethene (BODIPY) dyes (acceptor), were designed. Dyads were synthesized via acid-catalyzed multicomponent reactions followed by Sonogashira coupling. In both dyads, the BODIPY and TAPP moieties are linked through phenylethynyl groups, which allow free rotation of the BODIPY dyes; that is, they can act as molecular rotors. This was supported by X-ray crystallographic and DFT-optimized structures. Spectroscopic studies also confirmed the presence of both TAPP and BODIPY dyes in dyads with no electronic interactions that are suitable for fluorescence resonance energy transfer (FRET). Very high energy transfer efficiency (ETE >99%) from the donor TAPP moiety to the acceptor BODIPY moiety on excitation at the TAPP part was observed. However, due to the non-fluorescent nature of naked BODIPY dyes, no fluorescence emission was observed from the BODIPY moiety in both dyads. With increasing solvent viscosities, emission from the BODIPY moieties increases due to the restricted rotation of the BODIPY moieties. Plotting the logarithms of the fluorescent intensity of dyad 5 and the viscosity of the solution showed a good linear correlation obeying a Förster–Hoffmann equation. Non-fluorescent dyad 5 in methanol became greenish-yellow fluorescent in a methanol/glycerol (1:1) solvent. Furthermore, with an increase in the temperature of the methanol/glycerol (1:1) system, as the viscosity decreases, the fluorescence also starts decreasing. Thus, dyad 5 is capable of sensing the viscosity of the medium via a FRET-based “Off-On” mechanism. This type of viscosity sensor with a very large pseudo-Stokes shift and increased sensitivity will be useful for advancing chemo-bio sensing and imaging applications.